Theory of Doping in Indirect Determination of Concentration and Mobility of Native Point Defects in Metal Oxides - Zbigniew Grzesik (Science Faculty of Chiang Mai University, 2019)
In the present paper the application of doping effect to the calculations of concentration and mobility of point defects in transition metal oxides has been discussed. The proposed method consists in determination of the deviation from stoichiometry and thereby the concentration of prevailing point defects in a given oxide from the influence of aliovalent additions on the formation kinetics of this oxide, i.e., from doping effect. The possibilities offered by this method have been illustrated using diluted binary Ni-Cr and Ni-Li alloys, from the oxidation rates of which the defect concentration and defect mobility in Ni1-yO have been calculated. It has been shown that the results of such calculations are in satisfactory agreement with experimentally determined data, using direct gravimetric method.